FAILURE TO BECOME A TNI SOLDIER: A PENOMONOLOGICAL STUDY OF YOUTH ASPIRATIONS IN INDONESIA: Kegagalan Menjadi Prajurit TNI: Studi Penomonologi Cita-Cita Pemuda di Indonesia - samsul arifin; Jefri Mailool (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Failure is a situation where someone is unable to achieve their desires or achieve their desired goals. There are many ways to deal with failure for someone who experiences failure. This study aims to determine how young people respond to failure and shift the form of failure from TNI Soldiers to professions outside the TNI Soldier. This study uses a qualitative phenomenological approach. Ten Respondents were randomly selected from different regions. Data collection techniques used were through interviews and analysis techniques through Creswell's steps, from organizing data to presenting and visualizing it with the help of Atlas TI software. The results showed that those who had experienced failure to become TNI Soldiers responded almost uniformly to negative and positive responses. Negative responses mostly mentioned a lack of transparency in the selection process and the absence of support and